If A ,B and C are nonzero real numbers then D=[b^2c^2 bc b+c] c^2a^2 ca c+a a^2b^2 ab a+b =?

Let  = b2c2bcb+cc2a2cac+aa2b2aba+bTaking bc common from R1, ca from R2 and ab from R3, we get = a2b2c2bc11c+1bca11a+1cab11b+1aInterchanging , C1 by C2, we get = -1a2b2c21bc1c+1b1ca1a+1c1ab1b+1aApplying R1 = R1 - R2  and R2 = R2 - R3, we get = -1a2b2c20cb-a1b-1a0ac-b1c-1b1ab1b+1a= -1a2b2c2 1cb-a1c-1b-ac-b1b-1a = -1a2b2c2b - a - cb-ab- ac-bb + c - b =-1a2b2c2 c - a - c + acb - acb + a  = -1a2b2c2 0 = 0 

  • 1
What are you looking for?